Code-Mix Analysis on Maudy Ayunda's YouTube Content Titled "The Science of Love-Maudy Ayunda's Booklist" - Yosi Septia Sari; Desi Sukenti (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This research analyzes the phenomenon of code-switching in the video titled â€œThe Science of Love-Maudy Ayunda's Booklist,â€ uploaded by Maudy Ayunda on a video-sharing platform. The research methodology involves data collection through video analysis to identify instances of code-switching between Indonesian and English in Maudy Ayunda's discourse. Following identification, an analysis is conducted to understand the reasons behind the use of code-switching and its impact on public communication. The research findings indicate that code-switching is employed to enrich information delivery, emphasize concepts, and reach a broader audience. This phenomenon reflects the cultural and linguistic complexity in multilingual societies. Code-switching also plays a role in social inclusion and effective communication. This study provides valuable insights into cross-cultural and cross-linguistic communication and its relevance in the context of globalization and social media.